Mentoring Women's Farmer Groups in Utilizing Yard Land as an Effort for Food Security in the Pandemic Period - Ratna Susanti; Suci Purwandari (LPPMPK-Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2022)
The objectives of this community service are: 1. assisting women farmer groups in the use of yard land, 2. educating women farmer groups in efforts to food security during the pandemic. This community service was carried out for 3 months, namely April, May, and June 2021 through the following methods: 1) lectures by the implementation team for the Women Farmer Group in Baran village, Cawas, Klaten who attended a total of 52 people regarding food security education in during the pandemic, 2) distribution of assistance for a number of vegetable seeds to be planted in a predetermined yard, 3) assistance in planting and using vegetables as a source of family nutrition. The result of this community service is that the women in Baran Village, Cawas, Klaten who are members of the Women Farmers Group have an independent business in the form of vegetable plants as a source of nutrition that can be used as a share of crop yields: from, by, for the Woman Farmer Group members.